2016
DOI: 10.1021/acs.organomet.6b00344
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Zinc Species with Ge–Zn and Sn–Zn Bonds: A Reversible Insertion of a Stannylene into a Zinc–Carbon Bond

Abstract: The tetrylenes Ge(Ar Me 6 ) 2 and Sn(Ar Me 6 ) 2 (Ar Me 6 = C 6 H 3 -2,6-(C 6 H 2 -2,4,6-(CH 3 ) 3 ) 2 ) reacted with dimethylzinc to afford the insertion products (Ar Me 6 ) 2 Ge-(Me)ZnMe ( 1) and (Ar Me 6 ) 2 Sn(Me)ZnMe (3), which feature Ge−Zn and Sn−Zn bonds as well as two-coordinate zinc atoms. Crystals of 1 were found to be unsuitable for X-ray crystallography, so the ethyl-substituted (Ar Me 6 ) 2 Ge(Et)ZnEt (2) was synthesized in a parallel way to provide crystals suitable for X-ray studies. These show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
1
18
0
2
Order By: Relevance
“…In most cases insertion of the tetrylene into the M−C bond was observed, however in the case of stannylene and trialkylgallium this reaction was found to be reversible under ambient conditions. Extension of this work towards other reversible M−C insertions was found to be successful with dimethylzinc and stannylene . Currently examples of reversible tetrylene reactions are limited to a handful of reports,,, thus showing great potential for this class of compounds towards catalysis, particularly Power's recent example of reversible elimination of H 2 from a stannylene …”
Section: Reversible Bond Activationsmentioning
confidence: 95%
“…In most cases insertion of the tetrylene into the M−C bond was observed, however in the case of stannylene and trialkylgallium this reaction was found to be reversible under ambient conditions. Extension of this work towards other reversible M−C insertions was found to be successful with dimethylzinc and stannylene . Currently examples of reversible tetrylene reactions are limited to a handful of reports,,, thus showing great potential for this class of compounds towards catalysis, particularly Power's recent example of reversible elimination of H 2 from a stannylene …”
Section: Reversible Bond Activationsmentioning
confidence: 95%
“…[28] The Ge(1)ÀZn(1) bond length (2.4615 (5) ) is comparable with the value (2.425(3) ) found in the related complex depicted in Figure 1IX [22] and it is longer than the Ge-Zn covalent bond (S cov Ge,Zn = 2.39 ). [28][29] In complex 3 the central Cu atom is three-coordinate by two chloride ions Cl(2) and Cl(2a), and the Ge(1) atom. The coordination polyhedron can be best described as a deformed triangle with bond angles Ge(1)-Cu(1)-Cl(2) (136.08(2)8) and Cl(2)-Cu(1)-Cl(2a) (103.89(3)8) as representative of the biggest deviations from ideal shape.…”
Section: Complex Synthesis and Characterizationmentioning
confidence: 99%
“…We set out to explore this reactivity by studying the interaction of PCO À and AsCO À towards Powersbis(terphenyl)stannylene Te r 2 Sn (Ter = 2,6-bis[2,4,6-trimethylphenyl]phenyl), which is monomeric owing to the presence of the bulky terphenyl substituents. [31,32] Surprisingly,there are only ah andful of studies on the reactivity of this stannylene (Scheme 1), which has been shown to react with water and alcohols, [33] as well as alkyl aluminum, gallium, [34] and zinc compounds, [35] but not, for example,with white phosphorus. [36] Herein, we report on the reactivity of PCO À and AsCO À towards Te r 2 Sn and demonstrate the thermally or photolytically induced decarbonylation of AsCO À ,which thereby acts as asource of As À towards amolecular species.…”
mentioning
confidence: 99%